2003
DOI: 10.1095/biolreprod.102.007625
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transduction Pathways Activated by Chorionic Gonadotropin in the Primate Endometrial Epithelial Cells1

Abstract: Successful implantation requires synergism between the developing embryo and the receptive endometrium. In the baboon, infusion of chorionic gonadotropin (CG) modulates both morphology and physiology of the epithelial and stromal cells of the receptive endometrium. This study explored the signal transduction pathways activated by CG in endometrial epithelial cells from baboon (BE) and human (HES). Incubations of BE and HES cells with CG did not significantly alter adenylyl cyclase activity or increase intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 46 publications
5
62
1
1
Order By: Relevance
“…In mouse uterus, a binding study and in situ hybridization technique revealed that LHR is localized in endometrial stromal cells (Zheng et al 2001). Several groups also proposed different paracrine functions of LH/HCG in endometrium-like prostaglandin and cytokine biosynthesis (Zhoi et al 1997, Rao 1998, Zhou et al 1999, Srisuparp et al 2003, and modulation of decidualization and implantation of the embryo into the uterus (Han et al 1999, Banaszak et al 2000, Licht et al 2002, Das et al 2009). The present study using RT-PCR and real-time PCR demonstrates a clear and distinct expression of Lhr mRNA in mouse endometrium at each stage of the estrous cycle with a maximum at metestrus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In mouse uterus, a binding study and in situ hybridization technique revealed that LHR is localized in endometrial stromal cells (Zheng et al 2001). Several groups also proposed different paracrine functions of LH/HCG in endometrium-like prostaglandin and cytokine biosynthesis (Zhoi et al 1997, Rao 1998, Zhou et al 1999, Srisuparp et al 2003, and modulation of decidualization and implantation of the embryo into the uterus (Han et al 1999, Banaszak et al 2000, Licht et al 2002, Das et al 2009). The present study using RT-PCR and real-time PCR demonstrates a clear and distinct expression of Lhr mRNA in mouse endometrium at each stage of the estrous cycle with a maximum at metestrus.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to this conventional belief, numerous studies demonstrated that the LH receptor (LHR)/HCG receptor is also present in a variety of non-gonadal tissues, particularly in the female reproductive tract (Bonnamy et al 1990, Reshef et al 1990, Lei et al 1993, Mukherjee et al 1994, Shemesh et al 1997, Ziecik et al 2005. Activation of this receptor in vivo and in vitro resulted in a wide variety of responses, which can be attributed to initiation and maintenance of pregnancy (Banaszak et al 2000, Srisuparp et al 2003, Lin et al 2005, Ziecik et al 2005.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Luteinizing hormone/hCG receptors are expressed in many reproductive organs and within specific regions within these organs. Endometrial tissues from numerous species have been reported to contain LH/hCG receptors [43][44][45]. In the human and nonhuman primate LH/hCG receptor expression appears to be cycle-dependent with secretory endometrium expressing higher levels compared to proliferative endometrium [46,47].…”
Section: Discussionmentioning
confidence: 99%